SERS multiplexing of methylxanthine drug isomers via host–guest size matching and machine learning. Issue 37 (20th August 2021) - Chio, Weng-I Katherine; Liu, Jia; Jones, Tabitha; Perumal, Jayakumar; Dinish, U. S.; Parkin, Ivan P.; Olivo, Malini; Lee, Tung-Chun
Abstract : Simultaneous quantification of drug isomers, methylxanthines (MeX), by SERS via self-assembly of gold nanoparticles (Au NPs) mediated by cucurbit[ n ]urils (CBs). Abstract : Multiplexed detection and quantification of structurally similar drug molecules, methylxanthine MeX, incl. theobromine TBR, theophylline TPH and caffeine CAF, have been demonstrated via solution-based surface-enhanced Raman spectroscopy (SERS), achieving highly reproducible SERS signals with detection limits down to ∼50 nM for TBR and TPH, and ∼1 μM for CAF. Our SERS substrates are formed by aqueous self-assembly of gold nanoparticles (Au NPs) and supramolecular host molecules, cucurbit[ n ]urils (CB n, n = 7, 8). We demonstrate that the binding constants can be significantly increased using a host–guest size matching approach, which enables effective enrichment of analyte molecules in close proximity to the plasmonic hotspots. The dynamic range and the robustness of the sensing scheme can be extended using machine learning algorithms, which shows promise for potential applications in therapeutic drug monitoring, food processing, forensics and veterinary science.